Ethnomathematics Of The Jejahitan In Balinese Hindu Ritual - Gede Ngurah Oka Diputra; I Gede Bagus Wisnu Bayu Temaja; Anak Agung Purwa Antara; I Wayan Sudiarta; I Wayan Nayun; I Made Yasna (Cita konsultindo, 2023)
Ethnomathematics is a mathematical concept contained in a culture. The presence of mathematics with cultural nuances will make a significant contribution to learning mathematics. One of the ethnomathematics objects in Balinese Hindu culture is the jejahitan which is used as a medium for learning geometry. Jejahitan is a means of praying for traditional Balinese Hindu ceremonies made of young coconut leaves or janur, dried doub palm leaves, with various supporting materials such as flowers and fruit. The jejahitan used in ethnomathematics objects such as taledan, lamak, ituk-ituk, ceniga, tamiang, serembeng daksina, and sampian kapit kacang/canang kojong. At the same time, the applied mathematical concepts (geometry) are square, rectangle, triangle, circle, trapezoid, cylinder, cone, symmetry, width, circumference and volume. Ethnomathematics is very important; apart from being a student learning material, it also serves as a cultural preservation venue.